Anthropogenic noise disrupts mate choice behaviors in female Gryllus bimaculatus. (2nd February 2021) - Bent, Adam M; Ings, Thomas C; Mowles, Sophie L
Abstract: By assessing the sexual signals produced by conspecifics, individuals can make informed decisions on the best choice of mate, which can lead to reproductive fitness benefits. However, these communication systems are often vulnerable to disruption by conflicting with stimuli present in the environment. Anthropogenic noise may act as one such disruptive stimulus, leading to inefficient mate choice decisions and, thus, reductions to an animal's fitness. In this study, the mate choice behaviors of female Gryllus bimaculatus were tested when presented with artificial male courtship songs of differing "quality" under different acoustic conditions. In ambient noise conditions, females significantly preferred mates paired with higher-quality songs, indicated by increased mating rates and reduced latency to mate. However, this mate selection pattern was disrupted in both traffic and white noise conditions. Additionally, "high-quality" courtship songs had an increased mounting latency in traffic and white noise conditions, when compared to ambient noise conditions. Making nonoptimal mating decisions, such as the ones seen here, can lead to deleterious fitness consequences, alter population dynamics, and weaken sexual selection, unless individuals adapt to cope with anthropogenic interference. Abstract : Female field crickets have different mating preferences when human-generated noise is present. Under ambient noise conditions, females mounted males paired with a "high-quality" song sooner and more frequently than those paired with a "low-quality" song or no song at all. These differences were not apparent when traffic or white noise was present. As acoustic courtships are used by many species, these findings have important implications for mate choice throughout the animal kingdom.